Dentists’ Preference of Pulp Capping Agent for Indirect Pulp Capping in Primary and Permanent Molars - An Observational Study - Maria Anthonet Sruthi1 , EMG Subramanian2 , Vignesh Ravindran (Institute of Medico-legal Publications Pvt Ltd, 2020)
One of the major challenges associated with indirect pulp capping is to prevent the exposure of the pulp andmaintain its vitality. It is based on the rationale that pulpal mesenchymal cells induce dentin bridge formation.The common pulp capping agents used are calcium hydroxide and mineral trioxide aggregate both of whichact based on their high pH. The aim of the study is to infer the most preferred pulp capping agent by dentistsin a private dental college so as to achieve a good prognosis after indirect pulp capping of primary andpermanent molars.A total of 297 restorative procedures were obtained after reviewing patient case sheetsand were analysed using descriptive statistics on SPSS Software. Among 139 treatment procedures, themost common pulp capping agent used was calcium hydroxide (69.1%) in primary molars and mandibularpermanent molars and MTA (30.9%) mostly in maxillary permanent molars. Within the limits of the study,calcium hydroxide was the preferred pulp capping agent for indirect pulp capping by dentists in a privatedental college in both primary and permanent molars. However, with its clinical advantages, mineral trioxideaggregate shows a promising candidate as an indirect pulp capping agent in primary and permanent teeth.